2021
DOI: 10.1007/s00477-020-01968-w
|View full text |Cite
|
Sign up to set email alerts
|

The Bayesian Susceptible-Exposed-Infected-Recovered model for the outbreak of COVID-19 on the Diamond Princess Cruise Ship

Abstract: The outbreak of COVID-19 on the Diamond Princess Cruise Ship provides an unprecedented opportunity to estimate its original transmissibility with basic reproductive number (R0) and the effectiveness of containment measures. We developed an ordinary differential equation-based Susceptible-Exposed-Infected-Recovery (SEIR) model with Bayesian underpinning to estimate the main parameter of R0 determined by transmission coefficients, incubation period, and the recovery rate. Bayesian Markov Chain Monte Carlo (MCMC)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Specifically, Sweden reported a seroprevalence of 7.3% in the Stockholm area in April 2020 despite mathematical models predicting an infection rate of 20-25% [24]. An interesting case study is that of the Diamond Princess cruise ship that in February 2020 was confronted with a COVID-19 outbreak while in the western Pacific ocean, and reported half of the global COVID-19 cases at that time outside China [25,26]. The infection rates on the cruise ship were mathematically projected to be higher than those occurring in open spaces because complete isolation was not possible, and members of the crew were also exposed to the virus.…”
Section: Glossarymentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, Sweden reported a seroprevalence of 7.3% in the Stockholm area in April 2020 despite mathematical models predicting an infection rate of 20-25% [24]. An interesting case study is that of the Diamond Princess cruise ship that in February 2020 was confronted with a COVID-19 outbreak while in the western Pacific ocean, and reported half of the global COVID-19 cases at that time outside China [25,26]. The infection rates on the cruise ship were mathematically projected to be higher than those occurring in open spaces because complete isolation was not possible, and members of the crew were also exposed to the virus.…”
Section: Glossarymentioning
confidence: 99%
“…The infection rates on the cruise ship were mathematically projected to be higher than those occurring in open spaces because complete isolation was not possible, and members of the crew were also exposed to the virus. Different studies have estimated the basic reproduction number (R 0 ) during the outbreak period in the ship to be between 5.71 and 14.8 [25,26], which suggests that the number of exposed individuals was higher than the number of those who actually became infected. Subsequently, in contrast to the officially reported 712 individuals with PCR-positive results for COVID-19, one study reported a calculation in which this number should have been at least 1000 [26].…”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation
“…., N T ) incident cases over consecutive time units, and a generation time distribution w, R 0 is estimated by these two methods: 2.2.2.1 Sequential Bayesian method (SB). This method relies on an approximation to the SIR model [39][40][41][42] whereby incidence at time t + 1, N(t + 1) is approximately Poisson distributed with mean…”
Section: Plos Onementioning
confidence: 99%
“…Various Bayesian methods have been employed for the epidemiological and related models for studying COVID-19, including the Bayesian MCMC algorithm for the inference of statistical and epidemiological parameters [18][19][20][21], Naïve Bayes method for feature classification in the diagnosis of COVID-19 [22], Bayesian network for severity classification [23,24], spatial geo-referencing analysis [25,26], etc. A few studies have already presented remarkable attempts on methodologies that integrate Bayesian inference with SIR-based compartmental models.…”
Section: Introductionmentioning
confidence: 99%